2019
DOI: 10.1111/andr.12727
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase 2 (COX2) expression and prostaglandin synthesis in neonatal rat testicular germ cells: Effects of acetaminophen and ibuprofen

Abstract: sentence: Neonatal rat testicular germ cell expresses COX2 and produces prostaglandins, and ibuprofen and acetaminophen alter their proliferation and differentiation. AbstractBackground: In infants, fever is often treated with acetaminophen or ibuprofen, two antipyretic and analgesic drugs inhibiting cyclooxygenases (COXs), enzymes catalyzing prostaglandin production. Infancy represents a critical developmental period when neonatal germ cells/gonocytes differentiate to spermatogonial stem cells required for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
0
21
0
1
Order By: Relevance
“…Interestingly, we recently reported that neonatal gonocytes express COX2 and other enzymes of the prostaglandin pathway, and produce prostaglandins (PG) E2 and PGF2a [19]. Moreover, blocking PGE2 and PGF2a synthesis with ibuprofen for 24 h correlated with a partial decrease in RA-induced differentiation in PND3 gonocytes [19].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, we recently reported that neonatal gonocytes express COX2 and other enzymes of the prostaglandin pathway, and produce prostaglandins (PG) E2 and PGF2a [19]. Moreover, blocking PGE2 and PGF2a synthesis with ibuprofen for 24 h correlated with a partial decrease in RA-induced differentiation in PND3 gonocytes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assessed using a Trypan blue exclusion assay, by counting live and trypan blue-positive gonocytes as previously described [19], and viability was expressed as the mean ± SEM of the percentage of live cells against the total number of gonocytes in 3 independent experiments, each performed with triplicates.…”
Section: Cell Viabilitymentioning
confidence: 99%
See 3 more Smart Citations